Letter to Governor Schwarzenegger regarding BHP Biliton's Proposed LNG Port - Krop, Linda
Letter to Governor Schwarzenegger from the Environmental Defense Center Chief Counsel Linda Krop regarding BHP Billiton's Proposed Cabrillo Port LNG Deepwater Port Project.